Identification of copy number variants contributing to hallux valgus - Zhou, Wentao; Jia, Jun; Qu, Hui-Qi; Ma, Feier; Li, Junyi; Qi, Xiaohui; Meng, Xinyi; Ding, Zhiyong; Zheng, Gang; Hakonarson, Hakon; Zeng, Xiantie; Li, Jin; et al. (Frontiers in Genetics, 2023)
Hallux valgus is a common form of foot deformity, and genetic factors contribute substantially to the pathogenesis of hallux valgus deformity. We conducted a genetic study on the structural variants underlying familial hallux valgus using whole exome sequencing approach. Twenty individuals from five hallux valgus families and two sporadic cases were included in this study. A total of 372 copy number variations were found and passed quality control filtering. Among them, 43 were only present in cases but not in controls or healthy individuals in the database of genomic variants. The genes covered by these copy number variations were enriched in gene sets related to immune signaling pathway, and cytochrome P450 metabolism. The hereditary CNVs demonstrate a dominant inheritance pattern. Two candidate pathogenic CNVs were further validated by quantitative-PCR. This study suggests that hallux valgus is a degenerative joint disease involving the dysregulation of immune and metabolism signaling pathways.